Solidification-joinability correlation of hypoeutectic aluminium casting alloys for self-piercing riveting (SPR) - Neuser, Moritz; Kaimann, Pia Katharina; Stratmann, Ina; Bobbert, Mathias; Klöckner, Johann Moritz Benedikt; Mann, Moritz; Hoyer, Kay-Peter; Meschut, Gerson; Schaper, Mirko (Journal of Manufacturing Processes)
One of the major topics in the modern automotive industry is reducing emissions and increasing the mileage range. To tackle this challenge, on the one hand, modifying the powertrain system is a possibility, and on the other hand, lightweight design offers various possibilities. Multi-Material Design (MMD) involves designing car bodies that combine different materials that require joining. Given the variety of materials, mechanical joining processes are preferred. Especially the current development of the Giga/Mega-casting process concerning aluminium casting and the subsequent mechanical joining illustrates the challenges of this material group. In car production, aluminium castings are mainly made from aluminium-silicon (AlSi) alloys. Ultimately, the alloy system's insufficient ductility leads to crack initiation during mechanical joining. Cast parts are therefore often used in areas of the car body that are exposed to high-pressure loads. For example, self-piercing riveting (SPR) is used due to its high load-bearing capacity. In this study, improved joinability is demonstrated by influencing the microstructure through tailored solidification rates and a developed heat-treatment chain strategy adapted for hypoeutectic AlSi systems. Data on microstructure, mechanical, and joining properties are used to develop a solidification-joining correlation for the SPR process across a range of Si contents and solidification rates. The purpose is to develop the ability to produce suitable aluminium castings with sufficient joinability, thereby improving versatility.
Keywords: Mechanical joining; Aluminium; Self-piercing riveting; Casting; Microstructure; Joinability AlSi-alloys

Mechanical joinability of microstructurally graded structural components manufactured from hypoeutectic aluminium casting alloys - Neuser, Moritz; Schlichter, Malte Christian; Hoyer, Kay-Peter; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko (44th Conference of the International Deep Drawing Research Group (IDDRG 2025))
Lightweight design is a driving concept in modern automotive engineering to minimize resource consumption over a vehicle's lifecycle through multi-material design, which relies on the use of joining techniques in car body fabrication. Multi-material design and the increasing trend towards producing large structural components using the megacasting process pose considerable challenges, particularly in the mechanical joining of aluminium-silicon (AlSi) castings. These castings typically exhibit low ductility and are prone to cracking when mechanically joined. Based on the excellent castability of hypoeutectic AlSi alloys, these are applied in sand casting and die casting as well as in megacasting. With a silicon content between 7 wt% and 12 wt%, these AlSi-alloys have a plate-like silicon phase that initiates cracks during mechanical joining. To enhance the joinability of castings, the research hypothesis is that improved solidification conditions enable a significant modification in the microstructure and therefore, increase the mechanical properties. During the manufacture of the castings using the sand casting process, the solidification conditions within the structural elements are varied to modify the microstructure to obtain castings with graded microstructure. The castings are evaluated using mechanical, microstructural and joining testing methods and finally, a microstructure-joinability correlation is established.
Keywords: Joining; Casting; Self-pierce riveting; Aluminium casting alloy

Bildauswertendes Verfahren zur Evaluierung der Mikrostruktur von AlSi-Systemen - Neuser, Moritz; Cichon, Gerrit; Hoyer, Kay-Peter; Schaper, Mirko (Bildauswertendes Verfahren zur Evaluierung der Mikrostruktur von AlSi-Systemen)
Aluminium-Silizium-Legierungen (AlSi) werden insbesondere bei der gießtechnischen Herstellung von Leichtbaukomponenten für Fahrzeuge verwendet. Dieses Legierungssystem hat hervorragende Gießeigenschaften bei gleichzeitig akzeptablen mechanischen Eigenschaften. Aufgrund des hohen Silizium-(Si)-Gehaltes, wodurch die Volumenkontraktion im Phasenübergang von flüssig-fest nahezu unterbunden wird, neigen AlSi-Legierungen dazu, feinere oder gröbere Si-Platten bei unterschiedlichen Erstarrungsgeschwindigkeiten zu bilden. Um die mechanischen Eigenschaften zu verbessern, werden dem Legierungssystem in der Schmelzphase entweder Natrium (Na) oder Strontium (Sr) zugesetzt. Dies hat zur Folge, dass sich eine fein lamellare Si-Morphologie bei der Erstarrung ausbildet; dies kann ebenfalls durch hohe Erstarrungsgeschwindigkeiten erreicht werden. Ein nachfolgendes Lösungsglühen bewirkt eine Sphäroidisierung der Si-Partikel und dient der Steigerung der Duktilität. Aktuell fehlen fundierte Erkenntnisse zur Ausprägung der Si-Morphologie in Abhängigkeit der Erstarrungsgeschwindigkeit oder infolge einer Wärmebehandlung. Vor diesem Hintergrund werden in dieser Studie verschiedene Behandlungsparameter in Bezug auf das Einformverhalten der Si-Partikel mit einem bildauswertenden Verfahren evaluiert sowie unter Bezug auf verschiedene chemische Zusammensetzungen miteinander korreliert.
Keywords: Bildauswertendes Verfahren; Mikrostrukturanalyse; AlSi-System; Si-Morphologie

Mechanical properties and joinability of the near-eutectic aluminium casting alloy AlSi12 - Neuser, Moritz; Holtkamp, Pia Katharina; Hoyer, Kay-Peter; Kappe, Fabian; Yildiz, Safak; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko (The Journal of Materials: Design and Applications, Part L)
One of the most important strategies for reducing CO2 emissions in the mobility sector is lightweight construction. In particular, the car body offers several opportunities for weight reduction. Multi-material designs are increasingly being applied to select the most suitable material for the respective load and ultimately achieve synergy effects. For example, aluminium castings are used at the nodes of a spaceframe body. Subsequently, these are joined with profiles to form the bodyshell. To join different materials mechanical joining techniques, such as semi-tubular self-piercing riveting, are deployed. According to the current state of the art, cracks occur in the aluminium castings during the mechanical joining process as a result of the high degree of deformation. Although the aluminium casting alloys of the AlSi-system exhibit low ductility, these alloys reveal excellent castability. In particular, the ability to cast thin structural parts is enabled by the low liquidus point of the near eutectic aluminium casting alloys. This study addresses the mechanical joining properties of the near eutectic aluminium casting alloy AlSi12, depending on different microstructures. These are achieved by annealing processes and modifying agents. Through an adapted heat treatment, the previously lamellar morphology can be transformed into a globular morphology, which leads to increased ductility and prevents the formation of cracks during the self-piercing riveting (SPR). The joinability is investigated using different die geometries, whereas the joint formation is analysed regarding crack initiation. To evaluate the increased ductility, microstructural and mechanical tests are performed and finally, a microstructure-joinability correlation is established.
Keywords: aluminium; casting; microstructure; joinability; self-piercing riveting

Thermomechanical Joining of Hypoeutectic Aluminium Cast Plates - Borgert, Thomas; Neuser, Moritz; Hoyer, Kay-Peter; Homberg, Werner; Schaper, Mirko (Journal of Manufacturing and Materials Processing)
Consistent lightweight construction in the area of vehicle manufacturing requires the increased use of multi-material combinations. This, in turn, requires an adaptation of standard joining techniques. In multi-material combinations, the importance of integral cast components, in particular, is increasing and poses additional technical challenges for the industry. One approach to solve these challenges is adaptable joining elements manufactured by a thermomechanical forming process. By applying an incremental and thermomechanical joining process, it is possible to react immediately and adapt the joining process inline to reduce the number of different joining elements. In the investigation described in this publication, cast plates made of the cast aluminium alloy EN AC-AlSi9 serve as joining partners, which are processed by sand casting. The joining process of hypoeutectic AlSi alloys is challenging as their brittle character leads to cracks in the joint during conventional mechanical joining. To solve this, the frictional heat of the novel joining process applied can provide a finer microstructure in the hypoeutectic AlSi9 cast alloy. In detail, its Si is finer-grained, resulting in higher ductility of the joint. This study reveals the thermomechanical joining suitability of a hypoeutectic cast aluminium alloy in combination with adaptively manufactured auxiliary joining elements.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Influence of thermo-mechanical joining process on the microstructure of a hypoeutectic aluminium cast alloy - Borgert, Thomas; Neuser, Moritz; Wiens, Eugen; Grydin, Olexandr; Homberg, Werner; Schaper, Mirko (Materials Research Proceedings)
Requirements of multi-material construction involve adjustments to standard joining techniques. Especially the growing importance of integral cast components poses additional engineering challenges for the industry. One approach to achieve these goals are adaptable joining elements formed by friction spinning. This approach uses friction-induced heat to form customisable joining elements to join sheets for different boundary conditions, even for brittle cast materials. It is possible to react immediately to adapt to the joining process inline and reduce the amount of different joining elements. As the joining partner serve casting plates of the aluminium casting alloy EN AC–AlSi9, which is processed in the sand casting. Joining hypoeutectic AlSi alloys constitutes a challenge because the brittle character of these cause cracks in the joint during conventional mechanical joining. Furthermore, the friction-induced heat of the novel joining process causes a finer microstructure in the hypoeutectic AlSi9 casting alloy. In particular, the eutectic Si is more fine-grained, resulting in higher joint ductility. This study indicates the joining suitability of a hypoeutectic aluminium casting alloy in combination with adaptive manufactured additional joining elements. Here, various mechanical and microstructural investigations validate the influence of the thermomechanical joining technique. In conclusion, the potential of this joining process is presented regarding the joinability of cast aluminium components.

Mechanical and Microstructure Characterisation of the Hypoeutectic Cast Aluminium Alloy AlSi10Mg Manufactured by the Twin-Roll Casting Process - Neuser, Moritz; Schaper, Mirko; Grydin, Olexandr (Journal of Manufacturing and Materials Processing)
Multi-material designs (MMD) are more frequently used in the automotive industry. Hereby, the combination of different materials, metal sheets, or cast components, is mechanically joined, often by forming joining processes. The cast components mostly used are high-strength, age-hardenable aluminium alloys of the Al–Si system. Here, the low ductility of the AlSi alloys constitutes a challenge because their brittle nature causes cracks during the joining process. However, by using suitable solidification conditions, it is possible to achieve a microstructure with improved mechanical and joining properties. For this study, we used the twin-roll casting process (TRC) with water-cooled rollers to manufacture the hypoeutectic AlSi10Mg for the first time. Hereby, high solidification rates are realisable, which introduces a microstructure that is about four times finer than in the sand casting process. In particular, it is shown that a fine microstructure close to the modification with Na or Sr is achieved by the high solidification rate in the TRC process without using these elements. Based on this, the mechanical properties increase, and especially the ductility is enhanced. Subsequent joining investigations validate the positive influence of a high solidification rate since cracks in joints can be avoided. Finally, a microstructure-property-joint suitability correlation is presented.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Influence of Shell Material on the Microstructure and Mechanical Properties of Twin-Roll Cast Al-Si-Mg Alloy - Grydin, Olexandr; Neuser, Moritz; Schaper, Mirko (Conference: ICTP 2023: Proceedings of the 14th International Conference on the Technology of Plasticity - Current Trends in the Technology of PlasticityAt: Cannes (France))

Mechanical Properties and Joinability of AlSi9 Alloy Manufactured by Twin‐Roll Casting - Neuser, Moritz; Kappe, Fabian; Ostermeier, Jakob; Krüger, Jan Tobias; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko; Grydin, Olexandr (Advanced Engineering Materials)
AlSi casting alloys combine excellent castability with high strength. Hence, this group of alloys is often used in the automotive sector. The challenge for this application is the brittle character of these alloys which leads to cracks during joint formation when mechanical joining technologies are used. A rise in ductility can be achieved by a considerable increase in the solidification rate which results in grain refinement. High solidification rates can be realized in twin–roll casting (TRC) by water-cooled rolls. Therefore, a hypoeutectic EN AC–AlSi9 (for European Norm - aluminum cast product) is manufactured by the TRC process and analyzed. Subsequently, joining investigations are performed on castings in as-cast and heat-treated condition using the self-piercing riveting process considering the joint formation and the load-bearing capacity. Due to the fine microstructure, the crack initiation can be avoided during joining, while maintaining the joining parameters, especially by specimens in heat treatment conditions. Furthermore, due to the extremely fine microstructure, the load-bearing capacity of the joint can be significantly increased in terms of the maximum load-bearing force and the energy absorbed.
Keywords: Condensed Matter Physics; General Materials Science

Influence of heat treatment on the suitability for clinching of the aluminium casting alloy AlSi9 - Neuser, Moritz; Böhnke, Max; Grydin, Olexandr; Bobbert, Mathias; Schaper, Mirko; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
In many manufacturing areas, multi-material designs are implemented in which individual components are joined together to form complex structures with numerous joints. For example, in the automotive sector, cast components are used at the junctions of the body and joined with different types of sheet metal and extruded profiles. To be able to join structures consisting of different materials, alternative joining technologies have emerged in recent years. This includes clinching, which allows assembling of two or more thin sheet metal and casting parts by solely cold forming the material. Clinching the brittle and usually less ductile cast aluminium alloys remains a challenge because the brittle character of the cast aluminium alloys can cause cracks during the forming of the clinched joint. In this study, the influence of the heat treatment time of an aluminium casting alloy AlSi9 on the joinability in the clinching process is investigated. Specific heat treatment of the naturally hard AlSi9 leads to a modification of the eutectic microstructure, which can increase ductility. Based on this, it will be examined if specific clinching die geometries can be used, which achieve an optimized geometrical formation of the clinched joint. The load-bearing capacities of the clinched joints are determined and compared by shear tensile and head tensile tests. Furthermore, the joints are examined microscopically to investigate the influence of the heat treatment on the failure behaviour during the load-bearing tests as well as crack initiation within the joining process.
Keywords: Mechanical Engineering; General Materials Science

Influence of solidification rates and heat treatment on the mechanical performance and joinability of the cast aluminium alloy AlSi10Mg - Neuser, Moritz; Grydin, Olexandr; Frolov, Y.; Schaper, Mirko (Production Engineering)
In modern vehicle chassis, multi-material design is implemented to apply the appropriate material for each functionality. In spaceframe technology, both sheet metal and continuous cast are joined to castings at the nodal points of the chassis. Since resistance spot welding is not an option when different materials are joined, research is focusing on mechanical joining methods for multi-material designs. To reduce weight and achieve the required strength, hardenable cast aluminium alloys of the AlSi-system are widely used. Thus, 85–90% of aluminium castings in the automotive industry are comprised of the AlSi-system. Due to the limited weldability, mechanical joining is a suitable process. For this application, various optimisation strategies are required to produce a crack-free joint, as the brittle character of the AlSi alloy poses a challenge. Thus, adapted castings with appropriate ductility are needed. Hence, in this study, the age-hardenable cast aluminium alloy AlSi10Mg is investigated regarding the correlation of the different thicknesses, the microstructural characteristics as well as the resulting mechanical properties. A variation of the thicknesses leads to different solidification rates, which in turn affect the microstructure formation and are decisive for the mechanical properties of the casting as well as the joinability. For the investigation, plates with thicknesses from 2.0 to 4.0 mm, each differing by 0.5 mm, are produced via sand casting. Hence, the overall aim is to evaluate the joinability of AlSi10Mg and derive conclusions concerning the microstructure and mechanical properties.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Clinching of Aluminum Materials – Methods for the Continuous Characterization of Process, Microstructure and Properties - Kupfer, Robert; Köhler, Daniel; Römisch, David; Wituschek, Simon; Ewenz, Lars; Kalich, Jan; Weiß, Deborah; Sadeghian, Behdad; Busch, Matthias; Krüger, Jan Tobias; Neuser, Moritz; Grydin, Olexandr; et al. (Journal of Advanced Joining Processes)
Clinching as a mechanical joining technique allows a fast and reliable joining of metal sheets in large-scale production. An efficient design and dimensioning of clinched joints requires a holistic understanding of the material, the joining process and the resulting properties of the joint. In this paper, the process chain for clinching metal sheets is described and experimental techniques are proposed to analyze the process-microstructure-property relationships from the sheet metal to the joined structure. At the example of clinching aluminum EN AW 6014, characterization methods are applied and discussed for the following characteristics: the mechanical properties of the sheet materials, the tribological behavior in the joining system, the joining process and the resulting material structure, the load-bearing behavior of the joint, the damage and degradation as well as the service life and crack growth behavior. The compilation of the characterization methods gives an overview on the advantages and weaknesses of the methods and the multiple interactions of material, process and properties during clinching. In addition, the results of the analyses on EN AW 6014 can be applied for parameterization and validation of simulations.
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Mechanical Properties and Joinability of AlSi9 Alloy Manufactured by Twin‐Roll Casting - Neuser, Moritz; Kappe, Fabian; Ostermeier, Jakob; Krüger, Jan Tobias; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko; Grydin, Olexandr (Advanced Engineering Materials)
AlSi casting alloys combine excellent castability with high strength. Hence, this group of alloys is often used in the automotive sector. The challenge for this application is the brittle character of these alloys which leads to cracks during joint formation when mechanical joining technologies are used. A rise in ductility can be achieved by a considerable increase in the solidification rate which results in grain refinement. High solidification rates can be realized in twin–roll casting (TRC) by water-cooled rolls. Therefore, a hypoeutectic EN AC–AlSi9 (for European Norm - aluminum cast product) is manufactured by the TRC process and analyzed. Subsequently, joining investigations are performed on castings in as-cast and heat-treated condition using the self-piercing riveting process considering the joint formation and the load-bearing capacity. Due to the fine microstructure, the crack initiation can be avoided during joining, while maintaining the joining parameters, especially by specimens in heat treatment conditions. Furthermore, due to the extremely fine microstructure, the load-bearing capacity of the joint can be significantly increased in terms of the maximum load-bearing force and the energy absorbed.
Keywords: Condensed Matter Physics; General Materials Science

Clinching of Aluminum Materials – Methods for the Continuous Characterization of Process, Microstructure and Properties - Kupfer, Robert; Köhler, Daniel; Römisch, David; Wituschek, Simon; Ewenz, Lars; Kalich, Jan; Weiß, Deborah; Sadeghian, Behdad; Busch, Matthias; Krüger, Jan Tobias; Neuser, Moritz; Grydin, Olexandr; et al. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Numerical and Experimental Investigation of Heat Transfer in the Solidification-Deformation Zone During Twin-Roll Casting of Aluminum Strips - Grydin, Olexandr; Mortensen, Dag; Neuser, Moritz; Lindholm, Dag; Fjaer, Hallvard G.; Schaper, Mirko (Light Metals 2022)

Effect of Solidification Rates at Sand Casting on the Mechanical Joinability of a Cast Aluminium Alloy - Neuser, Moritz; Grydin, Olexandr; Andreiev, Anatolii; Schaper, Mirko (Metals)
Implementing the concept of mixed construction in modern automotive engineering requires the joining of sheet metal or extruded profiles with cast components made from different materials. As weight reduction is desired, these cast components are usually made from high-strength aluminium alloys of the Al-Si (Mn, Mg) system, which have limited weldability. The mechanical joinability of the cast components depends on their ductility, which is influenced by the microstructure. High-strength cast aluminium alloys have relatively low ductility, which leads to cracking of the joints. This limits the range of applications for cast aluminium alloys. In this study, an aluminium alloy of the Al-Si system AlSi9 is used to investigate relationships between solidification conditions during the sand casting process, microstructure, mechanical properties, and joinability. The demonstrator is a stepped plate with a minimum thickness of 2.0 mm and a maximum thickness of 4.0 mm, whereas the thickness difference between neighbour steps amounts to 0.5 mm. During casting trials, the solidification rates for different plate steps were measured. The microscopic investigations reveal a correlation between solidification rates and microstructure parameters such as secondary dendrite arm spacing. Furthermore, mechanical properties and the mechanical joinability are investigated.

Joining suitability of cast aluminium for self-piercing riveting - Neuser, Moritz; Kappe, Fabian; Busch, M; Grydin, Olexandr; Bobbert, Mathias; Schaper, Mirko; Meschut, Gerson; Hausotte, T (IOP Conference Series: Materials Science and Engineering)

Experimentelle bruchmechanische Untersuchung eines clinchgeeigneten Bleches aus HCT590X mithilfe einer neuen Probengeometrie - Weiß, Deborah; Schramm, Britta; Neuser, Moritz; Grydin, Olexandr; Kullmer, Gunter

Influence of Nozzle Shape on Near-Surface Segregation Formation During Twin-Roll Casting of Aluminum Strips - Grydin, Olexandr; Stolbchenko, Mykhailo; Schaper, Mirko (Light Metals 2020)